Neoadjuvant chemoradiotherapy of pancreatic cancer induces a favorable immunogenic tumor microenvironment associated with increased major histocompatibility complex class I‐related chain A/B expression. Issue 3 (12th June 2017) - Murakami, Takashi; Homma, Yuki; Matsuyama, Ryusei; Mori, Ryutaro; Miyake, Kentaro; Tanaka, Yusaku; Den, Kanechika; Nagashima, Yoji; Nakazawa, Masatoshi; Hiroshima, Yukihiko; Ueda, Michio; Tanaka, Kuniya; et al.
Abstract : Background: Damage‐associated molecular patterns (DAMPs) are related to immune responses in malignant tumors including tumor‐infiltrating lymphocytes (TILs). The aim of the present study was to determine the relationship between expression of components of DAMPs and TILs in pancreatic cancer patients who underwent neoadjuvant chemoradiotherapy (NACRT) versus those who did not. Methods: NACRT was administered to 51 patients with borderline‐resectable pancreatic cancer and not to 33 patients with resectable pancreatic cancer. Resected specimens were analyzed for the presence of DAMPs, major histocompatibility complex class I‐related chain A/B (MICA/B), and CD8 + TILs, CD4 + TILs, and forkhead box P3 positive (Foxp3 + ) TILs. The Treg/TIL ratio was obtained by dividing the number of Foxp3 + TILs, a surrogate for regulatory T cells, by the sum of CD8 + and CD4 + TILs. Results: Overexpression of calreticulin, Hsp70, and MICA/B were all significantly correlated with NACRT administration. In the NACRT group, high MICA/B expression was associated with a low Treg/TIL ratio, indicating a favorable immunogenic tumor microenvironment. Patients with a lower Treg/TIL ratio had longer survival. Conclusions: Overexpression of MICA/B, a component of DAMPs induced by NACRT, may play an important role in acquiring a favorable immune response for pancreatic cancer which contributes to longer survival, suggesting the potential of immunotherapy of this recalcitrant disease, especially for patients with overexpression of DAMPs.